Conservation and diversification of an ancestral chordate gene regulatory network for dorsoventral patterning - Kozmikova, Iryna; Smolikova, Jana; Vlcek, Cestmir; Kozmik, Zbynek (PloS one, 2011)
Formation of a dorsoventral axis is a key event in the early development of most animal embryos. It is well established that bone morphogenetic proteins (Bmps) and Wnts are key mediators of dorsoventral patterning in vertebrates. In the cephalochordate amphioxus, genes encoding Bmps and transcription factors downstream of Bmp signaling such as Vent are expressed in patterns reminiscent of those of their vertebrate orthologues. However, the key question is whether the conservation of expression patterns of network constituents implies conservation of functional network interactions, and if so, how an increased functional complexity can evolve. Using heterologous systems, namely by reporter gene assays in mammalian cell lines and by transgenesis in medaka fish, we have compared the gene regulatory network implicated in dorsoventral patterning of the basal chordate amphioxus and vertebrates. We found that Bmp but not canonical Wnt signaling regulates promoters of genes encoding homeodomain proteins AmphiVent1 and AmphiVent2. Furthermore, AmphiVent1 and AmphiVent2 promoters appear to be correctly regulated in the context of a vertebrate embryo. Finally, we show that AmphiVent1 is able to directly repress promoters of AmphiGoosecoid and AmphiChordin genes. Repression of genes encoding dorsal-specific signaling molecule Chordin and transcription factor Goosecoid by Xenopus and zebrafish Vent genes represents a key regulatory interaction during vertebrate axis formation. Our data indicate high evolutionary conservation of a core Bmp-triggered gene regulatory network for dorsoventral patterning in chordates and suggest that co-option of the canonical Wnt signaling pathway for dorsoventral patterning in vertebrates represents one of the innovations through which an increased morphological complexity of vertebrate embryo is achieved.
Keywords: Xenopus laevis; homeodoménové proteiny; Amino Acid Sequence; Homeodomain Proteins; Animals; Gene Regulatory Networks; molekulární sekvence - údaje; Oryzias; kultivované buňky; Humans; sekvence nukleotidů; 5' Untranslated Regions; Gene Expression Regulation, Developmental; sekvence aminokyselin; Molecular Sequence Data; protein goosecoid; genové regulační sítě; vývojová regulace genové exprese; Zebrafish; genetická variace; Evolution, Molecular; dánio pruhované; konzervovaná sekvence; Cells, Cultured; Sequence Homology, Amino Acid; 5' nepřekládaná oblast; Chordata; zvířata; fylogeneze; Conserved Sequence; Base Sequence; rozvržení tělního plánu; embryo nesavčí; Goosecoid Protein; lidé; Embryo, Nonmammalian; sekvenční homologie aminokyselin; Phylogeny; Body Patterning; Genetic Variation; molekulární evoluce